RANCANG BANGUN SISTEM PEMBAYARAN MANDIRI PADA WAHANA PERMAINAN - Endaryono, Pratama Johansah; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems, 2014)
ABSTRACTThis tool is designed to provide ease in self-contained payment system on rides. So that gives you comfort and safety for users of the game on the spacecraft itself. Utilization of EEPROM data storage media as the balance of the game, is expected to be beneficial to fans of the game. The function of this tool is to use a standalone payment or independent media that each rides installed these tools, so that users can directly use the rides, without having to pay in advance, just stay put card EEPROM to the tool. But users should also see remaining balance that exists there how to player EEPROM, can access the rides.In view of this there is a tool out of the LCD screen to see the remaining balance on card EEPROM and the process of doing so. There are 2 buttons, button 1 button 2 to play and to see the remaining balance on card EEPROM. There are several indicators LED to the passage of the game process. And to the Minimum, use a Microcontroller System ATmega32. The way this tool work is quite simple, but has a usability and functionality of the application in the real world.